Nanomaterials Preparation by Thermolysis of Metal Chelates - Uflyand, Igor E. (Springer Series on Polymer and Composite Materials,, 2018)
The book focuses on the thermal transformations of various types of metal chelates, e.g. low molecular weight and polymeric metal chelates, coordination polymers and metal-organic frameworks. It analyzes the major advances and the problems in the preparation of metal oxide materials, mixed-oxide nanocomposites, carbon materials and polymer derived non-oxide nanocomposites by the thermolysis of different metal chelates. It also highlights the influence of the spatial and electronic structure of metal chelates on the mechanism and kinetics of their thermal transformations, and discusses important issues like conjugate thermolysis and computer modelling of the thermolysis process. This book is useful for researchers experienced in thermolysis as well as for young scientists interested in this area of science.